Coping Stress pada Lansia di Pondok Pesantren Lansia Nurul Iman Karanganyar - Fadillah, Galih; Deslinda, Gadis; Prastyo, Bagus (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Elderly in the Nurul Iman Islamic Boarding School for the Elderly often face emotional challenges such as feelings of marginalization, loss of purpose, difficulty accepting declining health, loss of a spouse or loved ones, and unpreparedness for death. If these feelings are continuously dwelled upon, they can lead to stress. The aim of this study is to describe the stress coping mechanisms of the elderly residing at the Nurul Iman Islamic Boarding School for the Elderly in Karanganyar. The research method used is qualitative with a phenomenological approach. The research location is at the Nurul Iman Islamic Boarding School for the Elderly in Karanganyar, located at Ngablak RT 01 RW 09, Papahan, Tasikmadu District, Karanganyar Regency. The subjects of this study are 3 individuals selected using purposive sampling technique. Data collection was conducted through interviews and observations. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results show that the elderly apply stress coping using emotion-focused coping. Furthermore, the subjects continue to strive to live their lives by accepting fate and being grateful for whatever happens. The subjects have formed new social groups at the Nurul Iman Islamic Boarding School for the Elderly in Karanganyar, engaging in activities such as religious study sessions, dhikr, and reading Iqro or the Quran. The conditions experienced by the subjects have enhanced their religiosity.